Experiments on the dynamics of density currents - Nasrollahpour, R. (Penerbit UTM Press, 2016)
Density currents occur when fluid of one density propagates along a horizontal boundary into fluid of a different density. In dam reservoirs, density currents are the main transport mechanism for the incoming sediments and they play an important role in redistribution of existing sediments. This paper aims to investigate velocity structure in the body of density currents. To this end, laboratory experiments were performed on density currents having various initial conditions and bottom slopes. Then, vertical velocity profiles were recorded in the body of density currents. The velocity structure of the currents was investigated by fitting equations to the wall and jet regions of the measured profiles, and the constants of the equations were yielded with R2 more than 0.80. Temporal and spatial evolution of density currents were also analysed to study the dynamics of the frontal region of the currents. It was observed that the currents having more bottom slope travel at a further distance. It was also found that 400% increase in the initial concentration of the currents can increase their frontal velocity up to 97%.